Das Tulherias a Amarante. Pode a literatura ser uma forma de história? - Ricardo Namora (Carnets)
This text will focus on the literary, historical and biographic treatment of Napoleon in Portuguese poet and biographer Teixeira de Pascoaes’ Napoleon, published in 1940. In this work, Pascoaes puts forward an eccentric philosophical system that aspires to rebuild history in a particular way – in Pascoaes’ own words, Napoleon is “the saint of History”. But there is also a side to him that seems to stand out: Napoleon the man, double-sided as himself and Bonaparte, two entities that rewrite a personal and historic epic. Two main questions will be addressed in this context: i) what does it take for a well-known poet and thinker to construe, towards the end of his literary career, a complex biographical system in which Napoleon stands as its central axis?; ii) which consequences can be drawn from thinking, as Pascoaes does both implicitly and explicitly, that history is a form of literature?